Analysis of environmental consequences occurring in the life cycle of a retail facility - Tomporowski, Daniel; Markiv, Taras (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
The increasing importance of environmental protection issues has recently forced a low–emission approach to investment processes. To accomplish the European Union's climate, energy and environmental goals, action is needed to achieve high levels of energy efficiency and low environmental damage. Among the energy–intensive sectors, construction deserves a distinction due to its leading share in gross energy consumption in developed countries. Therefore, it is necessary, and at the same time more and more popular, to analyse the environmental loads generated in individual phases and throughout the life cycle of building objects. This subject is also gaining importance in the context of the recent increases in the prices of energy carriers, which forces the search for new construction and exploitation solutions in line with the philosophy of sustainable development and the circular economy. The aim of the analysis was to assess the environmental consequences in the life cycle of a real commercial building located in Janikowo (Kuyavian–Pomeranian Voivodeship), which was carried out using the LCA (Life Cycle Assessment) methodology. The obtained results indicated the dominance of the facility exploitation phase in the level of cumulative environmental loads.